1953
DOI: 10.1002/cber.19530861002
|View full text |Cite
|
Sign up to set email alerts
|

Über pflanzliche Herzgifte, XXIV. Mitteil.: Die quantitative Trennung und Identifizierung von Herzgiftglykosiden aus Digitalis purpurea und lanata durch “echte Verteilungschromatographie an Papier”

Abstract: Durch Tränken von Filtrierpapier mit einer Phase eines geeigneten zweiphasigen Lösungsmittelgemisches, während die andere Phase zum Entwickeln des Glykosidgemisches verwendet wird, läßt sich eine ausgezeichnete Trennung von Herzgiften unter kreisförmiger Lokalisierung auf dem Papier erreichen. Dieses Verfahren wird als “echte Verteilungschromatographie an Papier” bezeichnet. Es lassen sich so Mengen bis 300 μg trennen und nachher in den Flecken quantitativ bestimmen. Es werden die bekannten colorimetrischen Be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

1955
1955
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…Hydroxyl, acetoxyl, and/or carbonyl groups are usually found along the hydrocarbon chains. A positive response to Kedde's reagent (15) suggested the presence of an ,ß-unsaturated 7-lactone. A strong ir absorption at 1750 cm-1 and a uv absorption maximum at 215.5 nm (€=7974) in EtOH supported the presence of this functionality.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Hydroxyl, acetoxyl, and/or carbonyl groups are usually found along the hydrocarbon chains. A positive response to Kedde's reagent (15) suggested the presence of an ,ß-unsaturated 7-lactone. A strong ir absorption at 1750 cm-1 and a uv absorption maximum at 215.5 nm (€=7974) in EtOH supported the presence of this functionality.…”
mentioning
confidence: 99%
“…Bullatacinone [2] gave negative results with Kedde's reagent (15) indicating that there is no ,ß-unsaturated 7-lactone ring. Weak uv end absorption at a maximum of 203.5 nm (e = 3799) showed a lack of the conjugated unsaturation usually found in these acetogenins.…”
mentioning
confidence: 99%
“…A positive reaction of calocin (1) with NalCL (6) indicated the presence of a vicinal diol arrangement in the molecule. The diagnostic color tests for 2-deoxy sugar, viz., the Xanthydrol reaction (7,8) and Keller-Kiliani reaction (9), exhibited by 1 in conjunction with its molecular formula C27H44O6 indicated it to be a pregnane (C21) glycoside of a 2-deoxy hexose, commonly reported to occur in plants of Asclepiadaceae family (1,2). Its ir spectrum displayed absorption bands due to hydroxyl groups at 3430 cm-1, but the absence of absorption in the carbonyl region suggested that its pregnane genin presumably contained a -CHOH-CH3 chain at C-17.…”
Section: Resultsmentioning
confidence: 99%
“…The viscous mass was cooled and repeatedly triturated with absolute EtzO (to remove excess of phenylhydrazide), yielding a D-cymaronic acid phenylhydrazide (9) which crystallized from MeOH-Et20 as colorless needles (0.6 mg) mp 150-153°[lit (13) mp 155°}. l-Oleandronic acid phenylhydrazide (10).-A solution of 8 (2 mg) in absolute EtOH (0.05 ml) was mixed with freshly distilled phenylhydrazine (0.04 ml) and heated as for 7, affording L-oleandronic acid phenylhydrazide (10) which crystallized from MeOH-Et20 as colorless needles (1.2 mg) mp 135-136°[lit (14,15)…”
Section: Methodsmentioning
confidence: 99%